The diagnosis and Management of HIV Associated Acquired Hemophilia A: A Case Series From Durban, South Africa - Dashini Pillay; Nadine Rapiti (SAGE Publishing, 2023)
Introduction: In acquired hemophilia A (AHA), the body produces auto-antibodies against Factor VIII. Although AHA is rare, with an incidence of 1.5 patients/1 million population/year, there is a strong association with human immunodeficiency virus (HIV) infection. The accurate interpretation of screening coagulation tests is critical to identify patients with AHA, as the mortality rate secondary to bleeding is high. Methods: This was a retrospective case series which included all newly diagnosed AHA patients that were referred to Hemophilia care unit at King Edward VIII Hospital, Durban, South Africa from January 2011 to December 2021. The clinical presentation and laboratory results were documented. Results: Five patients were included in this case series. All patients were females aged between 28 and 64 years of age and they were HIV seropositive. They presented with spontaneous cutaneous and intramuscular bleeding. Four patients were virologically suppressed on anti-retroviral therapy, and no patient had a family history of congenital bleeding diathesis. Laboratory investigations confirmed AHA with high Factor VIII inhibitor titers, which ranged from 41 to 900 Bethesda Units (BU). All patients were managed with bypassing agents and oral corticosteroids. The monitoring of patients after the initiation of treatment was difficult as they all defaulted treatment. Conclusion: In view of the prevalence of HIV in sub-Saharan Africa, there is a possibility that AHA is under-diagnosed in our setting. The clinician and the laboratory have a combined critical role in identifying patients with AHA as the investigation of a prolonged APTT is mandatory. There are challenges in managing AHA patients in a resource-constrained setting.